2006
DOI: 10.1159/000094414
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium-Independent Flow-Induced Dilation in the Mouse Carotid Artery

Abstract: Background: We investigated the locus of flow regulation of vascular tone in carotid arteries of C57 Bl/6 and eNOS–/– mice. Methods: Arterial segments (2–3 mm) were mounted in a perfusion myograph and preconstricted with 1 µM phenylephrine before monitoring flow-induced changes in lumen diameter. Results: Both control and eNOS–/– mice demonstrated flow-dependent relaxation. This response was not attenuated by the NO synthase antagonist L-NAME, the cyclooxygenase inhibitor indomethacin, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…Carotid arteries were used because the associated flow conditions are well defined 29 and gene expression in these vessels can be manipulated by pluronic gel-based delivery. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Carotid arteries were used because the associated flow conditions are well defined 29 and gene expression in these vessels can be manipulated by pluronic gel-based delivery. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Shear stress is nearly universally associated with vasodilation in the peripheral vasculature, where research has consistently demonstrated a predominant vasodilatory response to blood flow in conduit arteries, such as femoral (205) and carotid (6,15,16,116,156) arteries, as well as resistance arteries and arterioles, including mesenteric arteries (16,23,98,116,123,188,234), coronary arteries (22,54,78,79,90,91,99,101,105,112,113,133,134,178,203,204,236,237), skeletal muscle feed arteries/arterioles (5-7, 55, 77, 86 -89, 96, 97, 166, 171, 180, 186, 187, 189, 190, 196, 202, 208, 228 -230), and adipose arterioles (153). Interestingly, shear stress is clearly capable of causing vasoconstriction in the cerebral circulation (20, 145,201).…”
Section: Mechanosensing In Endothelial Cells: Vasodilationmentioning
confidence: 99%
“…Fibronectin has also been recently shown to upregulate PKG in vascular SMCs as well as in aortic walls [7]. More functional studies also show that integrin engagement and activation induces vasodilation of different blood vessels [44][45][46]. Similarly, activating Epac induces SMC relaxation and vasodilation [47,48].…”
Section: Discussionmentioning
confidence: 99%